Clinical practice guideline for the management of early-stage cervical cancer - Malca-Tocas, Mirtha Magaly (2021)
Background: This article summarizes the clinical practice guideline (CPG) for the management of early-stage cervical cancer (IA1, IA2, IB1, IB2 o IIA1) in the Social Security of Peru (EsSalud). Objective: To provide clinical recommendations based on evidence for the management of early-stage cervical cancer in EsSalud. Material and methods: A CPG for the management of early-stage cervical cancer in EsSalud was developed. To this end, a guideline development group (local GDG) was established, including medical specialists and methodologists. The local GDG formulated 8 clinical questions to be answered by this CPG. Systematic searches of systematic reviews and -when it was considered pertinent- primary studies were conducted in Pubmed, Embase y CENTRAL during 2017 - 2018. The evidence to answer each of the posed clinical questions was selected. The quality of the evidence was evaluated using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology. In periodic work meetings, the local GDG used the GRADE methodology to review the evidence and formulate the recommendations, points of good clinical practice, and the flowchart of management. Finally, the CPG was approved with Resolution No. N° 27-IETSI-ESSALUD-2020. Results: This CPG addressed 8 clinical questions on the management of early-stage cervical cancer (IA1, IA2, IB1, IB2 o IIA1). Based on these questions, 10 recommendations (2 strong recommendations and 8 weak recommendations), 7 points of good clinical practice, and 4 flowcharts were formulated. Conclusion: This article summarizes the methodology and evidence-based conclusions from the CPG for the management of early-stage cervical cancer in EsSalud.